Rancang Bangun Sistem Kontrol dan Monitoring Lampu dan Air Conditioner Berbasis Blynk - Andi Frianto Perangin Angin; Markus Bernandos; Bucer Wycliffe Blegur Boling; Husam Harits Anggororundoyo Naufal; Imanuel Sakeus Antaribaba; Komang Jyoti Swari Laksmi Wati Wati (SKY EAST: Education of Aviation Science and Technology, 2024)
The use of lights and air conditioners (AC) in cadet dormitories sometimes often forget to turn off when not in use so that this becomes a waste of electrical energy and can cause a short circuit. So, the research objective is to develop an efficient solution for users to control and monitor electrical devices in a system. The system development process begins with selecting the appropriate hardware for control and monitoring needs using the NodeMCU ESP8266 microcontroller and additional components such as relay modules to control loads and PZEM-004T sensors that can function like kWH meters. In addition, it also uses the Blynk IoT application as a user interface that allows users to control and monitor electrical devices through mobile devices. So this research method is a development that will be tested to determine the feasibility of a tool. The result is that the developed tool has good test results and can be applied in the cadet dormitory.